EVALUASI TATA LETAK PARKIR TERHADAP KENYAMANAN PELANGGAN MELALUI KEPUASAN PELAYANAN PARKIR DI BORNEO SUPERMARKET KOTA NANGA BULIK - Ongki Ongki; Achmad Syamsudin; Indah Nur Oktavia; Agustina Muliyani (Penerbit Lafadz Jaya, 2026)
This research was conducted to determine the extent to which parking layout affects customer comfort through parking attendant satisfaction at Borneo Supermarket in Nanga Bulik City. Changes in the community's needs for parking services that prioritize speed, comfort, and safety are the basis for the importance of this research. The approach used was a quantitative method through the distribution of questionnaires to 100 respondents who were visitors or customers at Borneo Supermarket in Nanga Bulik City who used two-wheeled and four-wheeled vehicles.Data analysis was performed using Structural Equation Modeling (SEM) with the help of SmartPLS version 3.0 software. partial least squares. Overall, the results of the study indicate that parking layout has a significant effect on parking service satisfaction, and parking service satisfaction has a significant effect on customer comfort. Parking service satisfaction is an important factor in shaping the level of customer comfort, acting as a mediating variable in the relationship between parking layout and customer comfort. These findings provide a basis for parking managers to continue improving service quality according to user needs.